2014
DOI: 10.1080/16864360.2014.881178
|View full text |Cite
|
Sign up to set email alerts
|

FE Analysis of Contact between Residual Limb and Socket during Simulation of Amputee Motion

Abstract: The contact pressure at the socket-residual limb interface is the most important parameter to evaluate comfort of leg prosthesis. Experimental works analyzed this parameter for typical postures and during walking of an amputee; but experimental tests require a real prototype of the socket equipped with transducers. To optimize socket design, this work presents a virtual approach based on a digital avatar of the patient wearing lower limb prosthesis. Our approach considers the integration of two different types… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 19 publications
0
2
1
Order By: Relevance
“…Colombo et al [30] reported a 200 kPa maximum contact pressure on the transfemoral residual limb surface which is slightly smaller than present findings. However, they evaluated the walking condition with several times of the body weight applied at the hip joint.…”
Section: Discussioncontrasting
confidence: 78%
“…Colombo et al [30] reported a 200 kPa maximum contact pressure on the transfemoral residual limb surface which is slightly smaller than present findings. However, they evaluated the walking condition with several times of the body weight applied at the hip joint.…”
Section: Discussioncontrasting
confidence: 78%
“…The current study presents a method to combine inverse FEM and freehand ultrasound-based indentation for the identification of the passive material properties of the soft tissues of the thigh. Factually, most of the studies dealing with FEM of the thigh do not personalise the material properties of soft tissues, and would rather turn to values from literature [1,[6][7][8]10]. Indeed, very few studies developed the necessary process to estimate the personalised mechanical behaviour of soft tissues, especially when large soft tissues thicknesses are involved, like in the thigh area.…”
Section: Discussionmentioning
confidence: 99%
“…This interface is critical in order to ensure an optimal tradeoff between load transmission and both comfort and the prevention of soft tissues injuries. This is the reason why a particular attention has been paid to the mechanical behaviour of soft tissues under contact loadings in the last decade [1][2][3]. One way to evaluate loadings at the interface is to design subject specific Finite Element (FE) models [2,[4][5][6].…”
Section: Introductionmentioning
confidence: 99%